Inheritance of resistance to pyrethroids in Triatoma infestans, the main Chagas disease vector in South America - Cardozo, Rubén Marino (2010)
An outbreak of pyrethroid resistance was recently detected in Triatoma infestans from northern Argentina. To analyze the inheritance of the resistant phenotype, we carried out experimental crosses between resistant (R) and susceptible (S) strains captured in Argentina during 2005. The R strain was collected from sprayed houses in the north of the province of Salta while the S strain was collected in the province of Chaco. Both strains were bred in the laboratory for reciprocal crosses (F1), intercrosses (F2) and backcrosses (BC). The descendents were tested by a standard insecticide resistance bioassay. Resistance ratios were 1 for S strain, 103.36 for R strain and 18.34 for F1. The regression lines of F1 generations (R. × S and S. × R) showed no significant differences and were closer to that of the R parents, indicating that inheritance of deltamethrin resistance in T. infestans is autosomal and incompletely dominant (D=0.20). Chi-square analysis from responses of intercross and backcross progenies rejected the hypothesis of a single gene being responsible for resistance. The minimum number of independent segregation genes was three, as calculated with Lande's method. The genetic basis here described for the resistant phenotype indicate that, under pyrethroid selective pressure, the resistant genotypes could be easily spread to susceptible insects from resistant individuals, posing a major threat to vectorial control of Chagas disease.